Improving Learning with Model Cooperative Learning SDN 4 Sambongrejo - Tri Dodok Suryatiningsih (Universitas Sebelas Maret, 2020)
The purpose of the study to improve learning was carried out in pre-cycle from the number of 18 students applying Cooperative Learning, teachers gave formative test questions, achieved the completeness of 9 students with a breakdown of 90 grades as many as 3 students, 80 grades as many as 3 students, obtained a score of 70 as many as 3 students, not yet 9 students, scored 60 as many as 5 students and 50 as many as 4 students, the highest score of 90 , the lowest value is 50 . Average value is 68. Learning cycle I number of 18 students, , who achieved completion as many as 12 students details a score of 90 as many as 4 students, a score of 80 as many as 4 students, who obtained a score of 70 as many as 4 students, who have not completed 6 students, the highest score of 90, the lowest score of 60. The average score of 74 cycle II learning from 18 students is a score of 90 as many as 6 students, a score of 80 as many as 6 students, a score of 70 as many as 6 students, a high score of 90 and a low score of 70 An average score of 80 is determined by kkm 70 school.